ANALISIS KINERJA UD DAYA PRIMA ABADI DENGAN PENDEKATAN MALCOLM BALDRIGECRITERIA FOR PERFORMANCE EXCELLENCE - Kukuh Prima Danu; Husendar; Nur Islami Dwi Nugroho; Muhammad Ikhfal Azmi; Yoiz Shofwa Shafrani (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
This study aims to analyze the management performance of UD Daya Prima Abadi, a business unit in the rural agribusiness sector located in Patikraja District, using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) framework. Using a descriptive qualitative design, data were collected through observation and in-depth interviews, which were then converted into quantitative values ​​using the ADLI (Approach, Implementation, Learning, and Integration) method. The results showed that UD Daya Prima Abadi obtained a total score of 601 points, which placed it in the category of Emerging Industry Leaders at the Average level. This score indicates that the business unit has a basic system that is running with positive results, but still requires continuous improvement, especially in aspects of customer focus and operational efficiency. The formulated development strategies include customer communication innovations that are adaptive to rural community conditions, stock optimization to prevent waste, and strengthening business ethics for business sustainability.